Phonetic complexity and stuttering in Arabic. (December 2013) - Al-Tamimi, Feda; Khamaiseh, Zaidan; Howell, Peter
Abstract: The current study investigated whether phonetic complexity affected stuttering rate in Jordanian Arabic speakers. Speakers were assigned to three age groups (6–11, 12–17 and 18+ years). An Arabic index of phonetic complexity (AIPC) was developed. Each word was given a score based on the number of complex phonetic properties out of a total of nine that it contained in the AIPC. The results showed that stuttering on function words for Jordanian Arabic did not correlate significantly with the AIPC score for any age group. The AIPC scores of content and function-content words correlated positively with stuttering rate for the 6–11 age group alone with the function-content words affecting fluency more severely than did the content words. The AIPC scores of stuttered function, content and stuttered function-content words were higher than those of fluent words. The non-stuttered words had lower AIPC scores than the stuttered corresponding classes. This showed that the higher the AIPC score on stuttered words, the greater the chance for these word categories to be stuttered. The AIPC factors that most affected fluency in Jordanian Arabic were place of articulation, manner of articulation, word length, word shape and consonant length. We conclude that Arabic is similar to other languages with regard to the loci of stuttering, their phonetic complexity and AIPC factors affecting stuttering most. The correlation between phonetic complexity and the order of the AIPC factors are different between Arabic and other languages.